Water Resource Management : Sustainability in an Era of Climate Change - McNabb, David E. (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book is about how water managers in the United States are responding to the call for increased effort to achieve sustainable supplies of clean fresh water for present and future generations. The author, himself a participant in the water supply chain, demonstrates that while water is indeed one of life's most essential commodities, in many parts of the United States it is one of the most stressed resources. Throughout the book the author illustrates both the good and the bad efforts taken or not taken by water and wastewater management with real life examples. This book will appeal to the educators, students, volunteers, elected officials, regulators, and other participants with a role in helping the suppliers of water and wastewater services to achieve their goals providing clean, safe water on a sustainable basis. David E. McNabb is Professor Emeritus and adjunct professor at Pacific Lutheran University, USA. He is an elected water and wastewater district commissioner for Hartstene Pointe Water and Sewer District. His previous works include A Comparative History of Commerce and Industry: Cultural, Social and Economic Perspectives in Britain, Germany, Japan and the United States (2015) and Energy Policy in the U.S. (2011).
Keywords: Social sciences.; Environmental management.; Environmental geography.; Water pollution.; Environmental sociology.; Environmental policy.; elektronické knihy; electronic books